Is Fair Benefit Sharing a Reality or A Fallacy? Implications for Effective Collaborative Forest Management at Echuya Central Forest Reserve, S. W. Uganda - Bugabo, Stephen Gumisiriza; Bitariho, Robert; Twinamatsiko, Medard (East African Nature and Science Organization, 2023)
It is generally accepted that equitable benefits sharing from protected areas (PAs) is a probable technique for both sustainable management and PA conservation. Evidence however, suggests that this might not be entirely true since such benefits might not be equitably shared among local communities as they would have wished. This research compares benefits received by Collaborative Forest Management (CFM) community members with those of non-CFM community members adjacent to Echuya Central Forest Reserve (ECFR). The study further assesses the most preferred benefits by local community members around ECFR and the perceived barriers to equitable benefit sharing. It provides insight into how benefit sharing under CFM influences the conservation of protected areas. We conducted 458 household interviews, 26 key informant interviews and 4 focus group discussions to obtain data from CFM and non-CFM community members, government institutions, conservation organisations and local community leaders around ECFR. Benefits received by community members include access to firewood, grass, medicinal plants, materials to make ropes, honey and bamboo rhizomes, livelihood project support, cash benefits and training. The preferred benefits in their descending order include agricultural support, financial support, ecotourism, and livestock farming. The failure to monitor the implementation of CFM activities and corruption hinder equitable benefit sharing and promote overexploitation of forest resources. This study recommends that the National Forestry Authority (NFA) should include forest-adjacent communities in budget frameworks in order to provide financial support for CFM activities. The NFA and conservation organisations working around ECFR need to enhance the monitoring of CFM activities to ensure transparency and equitable sharing of forest resources